GAYA BAHASA KIASAN DALAM KUMPULAN CERPEN NURANI RINA KARYA DIAN YASMINA FAJRI - Erlina Erlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research is motivated by the style of figurative language in a collection of Short Stories Nurani Rina by Dian Yasmina Fajri. This study aimed to describe the Style of Figurative Language that are simile, personification, allusions, ironic, epithets, paronomasia in a collection of short stories Nurani Rina by Dian Yasmina Fajri. The research is a qualitative descriptive method. The object of this study was a collection of short stories Nurani Rina by Dian Yasmina Fajri. The data collection techniques used is given a code style of figurative language in a collection of short stories Nurani Rina by Dian Yasmina Fajri. Data analysis techniques in this study are: (a) Read the whole object, (b) Make a group of data that has been given a coding based on style of figurative language in a collection of short stories of Nurani Rina by Dian Yasmina Fajri, (c) Conducting discussions by analyzing the style of figurative language contained in the data, (d) Make conclusions and recommendations of the study. In this research the writer found 52 of styles of figurative language. 32 personification, 15 simile, 2 allusions, and 1 epithet. The conclusion from this study is that in a collection of short stories Nurani Rina by Dian Yasmina Fajri more common style of personification, and the least discovered is epithet and paronomasia.Keywords: style, figurative, short stories.